Human Rights for Life. The Experience of Ukraine (Journal of Legal Studies, 2018)
The article reveals the peculiarities of the normative and legal consolidation of the human right to life. The authors pay attention to the provisions of the decisions of the Constitutional Court of Ukraine that carry out the interpretation of the human right to life.